Assessment of perinatal anxiety: diagnostic accuracy of five measures - Ayers, S; Coates, R; Sinesi, A; Cheyne, H; Maxwell, M; Best, C; McNicol, S; Williams, LR; Uddin, N; Hutton, U; Howard, G; Shakespeare, J; et al. (Royal College of Psychiatrists, 2024)
Background Anxiety in pregnancy and after giving birth (the perinatal period) is highly prevalent but under-recognised. Robust methods of assessing perinatal anxiety are essential for services to identify and treat women appropriately.